CAREER OPPORTUNITIES FOR MANDARIN INTERPRETERS IN CENTRAL SULAWESI'S MINING SECTOR - Sri Khaerani Rahman; Annisa Syauqina Kadar; Sri Wahyuningsih; Nirdayanti Mustarih (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to analyze the essential role of Mandarin interpreters in the context of business communication within the mining sector, with a specific focus on the Indonesia Morowali Industrial Park (IMIP) in Central Sulawesi Province. T he necessity for effective cross-linguistic communication becomes paramount for multinational companies. Mandarin, as one of the most widely spoken languages globally, plays a central role in facilitating interactions between local stakeholders and foreign enterprises. This research employs a qualitative methodology through in-depth interviews with five interpreters operating at IMIP. The primary focus of this study is to explore the language and cultural challenges faced by interpreters and how they overcome these barriers to ensure accurate and effective communication. Additionally, the research examines the importance of understanding relevant technical terminology and cultural contexts in enhancing business relationships, operational effectiveness, and negotiation strategies. The findings indicate that qualified interpreters play a crucial role in maintaining smooth business operations, strengthening cross-cultural collaboration, and ensuring compliance with industry regulations. This study identifies the skills, qualifications, and experience necessary for interpreters to succeed in a dynamic and challenging work environment. Thus, it provides valuable guidance for individuals interested in pursuing a career as Mandarin interpreters in this evolving mining sector. In conclusion, the career prospects for Mandarin interpreters in the mining sector of Central Sulawesi are promising, given the increasing demand for effective cross-cultural communication to support multinational business growth